Pd-Catalyzed regio- and enantioselective allylic substitution with 2-pyridones. Issue 87 (16th October 2019) - Khan, Sardaraz; Shah, Babar Hussain; Khan, Ijaz; Li, Meiqi; Zhang, Yong Jian
Abstract : An efficient method for the asymmetric synthesis of N -substituted 2-pyridones via a Pd-catalyzed regio- and enantioselective allylic substitution of hydroxyl-containing allylic carbonates with 2-pyridones has been developed. Abstract : An efficient method for the asymmetric synthesis of N -substituted 2-pyridones via Pd-catalyzed regio- and enantioselective allylic substitution of hydroxyl-containing allylic carbonates with 2-pyridones has been developed. By using a palladium complex in situ generated from Pd2 (dba)3 ·CHCl3 and phosphoramidite L2 as a ligand, the process allowed rapid access to N -substituted 2-pyridones with complete chemo- and regioselectivities and good to high enantioselectivities.